The Role of Point-of-Care Ultrasound in Pilonidal Sinus Disease - Hadiel Kaiyasah; Lamis Aboufool; Labib Al Ozaibi (CINQUILL Medical Publishers Inc., 2022)
Pilonidal sinus is a common problem encountered in proctology clinics. It has a wide spectrum of clinical picture ranging from a single asymptomatic pit to a more complex disease with multiple sinuses and secondary openings. Hence, the treatment options could range from observation or simple excision to a more radical approach like flap surgeries. Ultrasonographic assessment could help in mapping the extent of the pilonidal sinus. It can also identify whether the sinus is infected or has formed an abscess. With the above-mentioned information provided by the point of care ultrasound, the surgeon can tailor the surgical approach to each individual case and improve the overall outcome. In this article, we are highlighting some examples of cases managed in our proctology unit where ultrasound was done preoperatively and guided the management.